The Effect Of Net Circumference Speed On Purse Seine Catches (Case Study: KM. Mekar Baru Putra 3) - Wulandari, Ully; Suharyanto, Suharyanto; Sutono, Dian; Maryanto, Yanto (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2023)
In March-July 2022, the research was conducted using the case study method on board the Mekar Baru Putra 3 Motor Ship based at the Nusantara Fishing Port in Pekalongan, Central Java. The aim is to determine the effect of the speed of purse seine net circumference on fish catches at KM Mekar Baru Putra 3 which is based on Pekalongan VAT. Data collection was carried out by survey method following fishing activities conducted by KM Mekar Baru Putra 3. The data collected are primary data in the form of: a) net circumference time, b) number of catches. Data was collected using stopwatches and stationery, then analyzed by regression analysis. In this study, the normality test results showed a significant value of 0.200. The value is greater than 0.05 which means the data is normally distributed. The results of the analysis were then carried out to see the linearity of pulling the wrinkle rope against the catch. From the test results, it is known that the value of Sig. deviation from linearity is 0.022 < 0.05, it is said that there is no linear relationship between the circular time speed and the catch.